Prevalence, symptom burden, and natural history of deep vein thrombosis in people with advanced cancer in specialist palliative care units (HIDDen): a prospective longitudinal observational study. Issue 2 (February 2019) - White, Clare; Noble, Simon I R; Watson, Max; Swan, Flavia; Allgar, Victoria L; Napier, Eoin; Nelson, Annmarie; McAuley, Jayne; Doherty, Jennifer; Lee, Bernadette; Johnson, Miriam J
Summary: Background: The prevalence of deep venous thrombosis in patients with advanced cancer is unconfirmed and it is unknown whether current international thromboprophylaxis guidance is applicable to this population. We aimed to determine prevalence and predictors of femoral deep vein thrombosis in patients admitted to specialist palliative care units (SPCUs). Methods: We did this prospective longitudinal observational study in five SPCUs in England, Wales, and Northern Ireland (four hospices and one palliative care unit). Consecutive adults with cancer underwent bilateral femoral vein ultrasonography on admission and weekly until death or discharge for a maximum of 3 weeks. Data were collected on performance status, attributable symptoms, and variables known to be associated with venous thromboembolism. Patients with a short estimated prognosis (<5 days) were ineligible. The primary endpoint of the study was the prevalence of femoral deep vein thrombosis within 48 h of SPCU admission, analysed by intention to treat. This study is registered with the ISRCTN registry, number ISRCTN97567719. Findings: Between June 20, 2016, and Oct 16, 2017, 343 participants were enrolled (mean age 68·2 years [SD 12·8; range 25–102]; 179 [52%] male; mean Australian-modified Karnofsky performance status 49 [SD 16·6; range 20–90]). Of 273 patients with evaluable scans, 92 (34%, 95% CI 28–40) had femoral deep vein thrombosis. Four participants with a scan showing no deep vein thrombosis on admission developed a deep vein thrombosis on repeat scanning over 21 days. Previous venous thromboembolism (p=0·014), being bedbound in the past 12 weeks for any reason (p=0·003), and lower limb oedema (p=0·009) independently predicted deep vein thrombosis. Serum albumin concentration (p=0·43), thromboprophylaxis (p=0·17), and survival (p=0·45) were unrelated to deep vein thrombosis. Interpretation: About a third of patients with advanced cancer admitted to SPCUs had a femoral deep vein thrombosis. Deep vein thrombosis was not associated with thromboprophylaxis, survival, or symptoms other than leg oedema. These findings are consistent with venous thromboembolism being a manifestation of advanced disease rather than a cause of premature death. Thromboprophylaxis for SPCU inpatients with poor performance status seems to be of little benefit. Funding: National Institute for Health Research (Research for Patient Benefit programme).